Inspecciones fitosanitarias del banano de exportacion en el muelle de Puerto Bolivar - Arias Carrasco, Jajaira Amabel (2011)
The inspection fhitosanitary the banana of exportation, to realize in the pier of Port Bolivar. The objectives to expound law of determine the problems fhitosanitary of banana of exportation the pier of Port Bolivar, to work during five day in the form first month of year 2010.In the pier to realize the teas two % of de boxes to enter, where to inspection the damage what caused the repulse of the fruit each. Date to search in the Leal of camp respective to facilitate for the company to verify of quality. To utilize in the experiment sketch of blocks o completed unforeseen fact taking for this case the month of evaluate how the treatment and the days of inspection how the repetition dude so a total of four treatment an five repetition with the what obtain twenty unity experimented in all the text. For the taking of date to search the information of the evaluate to realize in each box. The analysis of varying for the damage fhytossnitary not dihedron signify statistic between their demonstrate that the repulsed by the presence of plague an illness. Adjustment to equality between this indicate, the number of boxes sound evaluate for the exportation is lower the obtain by to repel of the fruit, with the lower to the determine an unfit hand ling. Of the fruit to level of campo because the effects fhitosanitarys most significantly will be with the process post harvest of each box the off act the quality of same to moment to be inspection in the Port of top us on board